2018
DOI: 10.3389/fonc.2018.00458
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Tumor Cell Resistance to the BCL-2 Inhibitor Venetoclax: A Product of Its Microenvironment?

Abstract: BCL-2 family proteins regulate the intrinsic pathway of programmed cell death (apoptosis) and play a key role in the development and health of multicellular organisms. The dynamics of these proteins' expression and interactions determine the survival of all cells in an organism, whether the healthy cells of a fully competent immune system or the diseased cells of an individual with cancer. Anti-apoptotic proteins like BCL-2, BCL-XL, and MCL-1 are well-known for maintaining tumor cell survival and are therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…However, BCL-2 antiapoptotic proteins extend well beyond BCL-2 and are known to be regulated by the microenvironment. 51 We uncovered that FL-FDC cocultures augmented tumor addiction to BCL-X L and MCL-1, whereas BFL-1 was relevant in FL-Mf cocultures. The consequence of these changes was a decrease in the activity of the BCL-2 inhibitor venetoclax.…”
Section: Discussionmentioning
confidence: 91%
“…However, BCL-2 antiapoptotic proteins extend well beyond BCL-2 and are known to be regulated by the microenvironment. 51 We uncovered that FL-FDC cocultures augmented tumor addiction to BCL-X L and MCL-1, whereas BFL-1 was relevant in FL-Mf cocultures. The consequence of these changes was a decrease in the activity of the BCL-2 inhibitor venetoclax.…”
Section: Discussionmentioning
confidence: 91%
“…In other hematologic cancers, the response rates were much lower, but combinations with standards of care yielded better results and led to the approval of venetoclax in combination with hypomethylating agents or low-dose cytarabine for the treatment of select patients with AML who cannot receive intensive induction chemotherapy (46,47). Despite these promising responses and exciting approvals, acquired resistance to venetoclax is beginning to emerge, and one mechanism identified preclinically is compensation by increased levels of MCL-1 (48). Although this could result from selection of subclones with preexisting MCL-1 overexpression, our data suggest that venetoclax can directly induce stabilization of MCL-1 by favoring its binding of BIM.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that the MCL1/NOXA complex plays a pivotal role in mediating acquired venetoclax resistance in MCL, and that such a resistance can be overcome by concurrent therapy with the MCL1 inhibitor S63845 [106,143,144]. The disruption of other BCL2 family members, including the upregulation of BCL-XL, loss of BIM, or mutation of BAX were all associated with acquired venetoclax resistance [145][146][147]. Mutations of the BH3 domain of BCL2 gene responsible for venetoclax binding (e.g., G101V and D103Y) were found in CLL patients with acquired resistance to venetoclax therapy [148].…”
Section: Resistance To Venetoclaxmentioning
confidence: 88%
“…Mutations of the BH3 domain of BCL2 gene responsible for venetoclax binding (e.g., G101V and D103Y) were found in CLL patients with acquired resistance to venetoclax therapy [148]. Dynamic changes of lymphoma cells in response to tumor microenvironment were repeatedly associated with venetoclax resistance [145]. Recently, complex transcriptional reprogramming with alteration of cell energy/metabolic pathways was identified as a key contributor to venetoclax resistance in lymphoma cells [149].…”
Section: Resistance To Venetoclaxmentioning
confidence: 99%